Applying and assessing the PEERS model on genetic counseling training in China: A mixed-method approach - Dong, Dong; Xiong, Shiyi; Nichini, Elena; Chen, Xiaoqiong; Liu, Binjuan; Zhu, Liling; Yip, Faustina Fu; Sun, Luming; Zhu, Jianfeng (Frontiers in Medicine, 2023)
Objective: Due to the changing medical demands in the healthcare system, there is a need for a standardised and professionalised curriculum for genetic counsellors. This mixed-method study will observe and evaluate the first Peer Experiential and Reciprocal Supervision (PEERS) training program on genetic counselling among medical practitioners in China; to provide feedback and recommendation for future training and practices. Method: A genetic counsellor training programme was held from December 10-11, 2016 in a foetal medicine unit and prenatal diagnosis centre in Shanghai with 59 participants from clinical centres, hospitals and organisations in China. An ethnographic reflexive assessment with a structured questionnaire were used to provide insights and feedback on the training experience. Results: Results indicate an inadequate mastery of genetic and foetal knowledge; lack of empathetic understanding and cultural sensitivity; difficulties in adopting a non-directive counselling approach; distance between reality and fictionality in the training; overall training’s helpfulness. Conclusion: The professionalization of genetic counselling in China is in the making with the soaring demands for genetic counselling services; this first experiment of PEERS training turned out to be needed, worth to be adapted towards medical centres across China, to better understand and face the challenges rising from genetic counselling practice.